2022
DOI: 10.3389/fpsyg.2021.678803
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Consumers’ Intention to Purchase Paid Stickers in Personal Messenger? The Role of Personality and Motivational Factors

Abstract: Many messengers and social networking services (SNSs) use emojis and stickers as a means of communication. Stickers express individual emotions well, allowing long texts to be replaced with small pictures. As the use of stickers increased, stickers were commercialized on a few platforms and showed remarkable growth as people bought and used stickers with their favorite characters, products, or entertainers online. Depending on their personality, individuals have different motivations for using stickers that de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…The study variables were developed from a critical literature review and applicable theoretical frameworks. 56 The personal traits used in the study were obtained from the big five personality traits, which include neuroticism, [45][46] extraversion, [38][39] openness to experience, [40][41][42][43][44][45] agreeableness, [40][41] and conscientiousness. [42][43][44][45] The engagement factors were represented by personal engagement and interactive engagement.…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study variables were developed from a critical literature review and applicable theoretical frameworks. 56 The personal traits used in the study were obtained from the big five personality traits, which include neuroticism, [45][46] extraversion, [38][39] openness to experience, [40][41][42][43][44][45] agreeableness, [40][41] and conscientiousness. [42][43][44][45] The engagement factors were represented by personal engagement and interactive engagement.…”
Section: Variablesmentioning
confidence: 99%
“…will recommend others to use emoticons while chatting Interactive Engagement I feel psychologically connected to others while using emoticons have pleasurable emotional state while using emoticons during interactions There is a sense of pride to be able to use emoticons during conversation Attitudes and expressions are displayed well using emoticons Personal Engagement I am able to express myself well while using emoticons I expresses my emotions well using emoticons during conversation[54][55] There is a sense of empowerment from engagement resulting from use of emoticons Using emoticons has a fulfilling and positive state of mind Source: Adapted from Kang et al, 56. …”
mentioning
confidence: 99%
“…intention to purchase. Kang et al (2022) and Sawmong (2022) indicate that stickers, which consist of emojis and emoticons, can be used as effective marketing communication tools. Both of these studies confirm that purchase or behavioral intentions were positively influenced by perceived ease of use due to the use of emojis and emoticons (in the form of stickers).…”
Section: 211mentioning
confidence: 99%
“…Sawmong (2022) also did not find a significant relationship between perceived usefulness and behavioral intentions due to the use of emojis and emoticons (in the form of paid stickers). However, Al-Maroof et al (2019) and Kang et al (2022) verify that perceived usefulness favorably impacted behavioral or purchase intentions due to stickers (emojis and emoticons). Other studies relating to online purchases and digital usage also suggested positive direct or indirect associations between perceived usefulness and purchase and/or behavioral intentions (Bravo et al, 2021;Al-Gasawneh et al, 2022;Leso and Cortimiglia, 2022), which leads to the following hypothesis:…”
Section: 211mentioning
confidence: 99%
See 1 more Smart Citation